2009
DOI: 10.1002/jcb.22242
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 inhibits the proliferation of human gingival fibroblasts via the EP2 receptor and Epac

Abstract: Elevated levels of prostaglandins such as PGE(2) in inflamed gingiva play a significant role in the tissue destruction caused by periodontitis, partly by targeting local fibroblasts. Only very few studies have shown that PGE(2) inhibits the proliferation of a gingival fibroblast (GF) cell line, and we expanded this research by using primary human GFs (hGFs) and looking into the mechanisms of the PGE(2) effect. GFs derived from healthy human gingiva were treated with PGE(2) and proliferation was assessed by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
5
23
0
1
Order By: Relevance
“…These results suggest that PGE 2 -mediated PAR2 internalization contributes to the inhibition of PAR2-signal transduction. PGE 2 increases cAMP levels in many cell types, and it has been reported that PGE 2 inhibits ERK phosphorylation in a cAMP-dependent manner [34]. In our experiments, both of PGE 2 and forskolin, increased intracellular cAMP levels (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…These results suggest that PGE 2 -mediated PAR2 internalization contributes to the inhibition of PAR2-signal transduction. PGE 2 increases cAMP levels in many cell types, and it has been reported that PGE 2 inhibits ERK phosphorylation in a cAMP-dependent manner [34]. In our experiments, both of PGE 2 and forskolin, increased intracellular cAMP levels (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…EP 2 and EP 4 receptors are coupled to G s protein, and the agonist stimulation of those receptors activates adenylyl cyclase, which generates cyclic AMP (cAMP), followed by activation of protein kinase A (PKA) and, perhaps, exchange protein activated by cAMP (Epac). [8][9][10][11][12][13] 16) and may play roles in peripheral and/or spinal nociceptive processing. 8) 4.…”
Section: Microsomal Prostaglandin E Synthase-1 Asmentioning
confidence: 99%
“…Activation of the Epac/Rap pathway by PGE 2 via EP 2 and EP 4 might also occur in synovial and gingival fibroblasts, playing a role in the pathologies of rheumatoid arthritis and inflammatory periodontal disease. 12,13) …”
Section: )mentioning
confidence: 99%
“…6B). We then treated the cells with PGD 2 or PGJ 2 together with IBMX, a nonselective phosphodiesterase inhibitor that boosts cAMP levels by preventing its degradation (41). IBMX, in conjunction with either PGD 2 or PGJ 2 , significantly enhanced the ability of PGD 2 or PGJ 2 to generate HA (Fig.…”
Section: Dp1 Activation Boosts Intracellular Camp To Increase Ha By Omentioning
confidence: 99%